Promoting Affordable Housing in Enhancing the Inclusiveness of Housing Policy - Noni Harianti Junaidi; Dani Salleh; Alphonsus Obberman Anchang (RIRAI Publisher, 2023)
Affordable housing has been debated among scholars as the tool used by various governments to address the issue of escalating housing prices in the open market segment. A lot of schemes, programs, and initiatives have been introduced by the State Government of Sarawak to increase the supply of affordable housing to be accessed by the public. However, there is no sign that the increase in housing market prices slowing down, and a lot of people still do not have access to public housing schemes. This paper focuses on the discussion of this issue in Sarawak. Besides, it also aims to measure the effectiveness and inclusiveness of the housing policy to resolve the housing scenario faced by the public. A qualitative method was used to collect data. Among the issues discussed in this study are the impact of government intervention in the open market, public-private sector partnership, and commitment of the financial institution. This study should be beneficial for the state government to capture the real issue of affordable housing in the state and be able to develop a more holistic and realistic housing policy in the future.